2016
DOI: 10.1038/srep26859
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotection of Liraglutide Against Ischaemia-induced Apoptosis through the Activation of the PI3K/AKT and MAPK Pathways

Abstract: Glucagon-like peptide-1 (GLP-1) is an incretin hormone that increases glucose-dependent insulin secretion to reduce the glucose level. Liraglutide, a long-acting GLP-1 analogue, has been found to have neuroprotective action in various experimental models. However, the protective mechanisms of liraglutide in ischaemic stroke remain unclear. Here, we demonstrated that liraglutide significantly decreased the infarct volume, improved neurologic deficits, and lowered stress-related hyperglycaemia without causing hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
121
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 40 publications
10
121
0
2
Order By: Relevance
“…Indeed, GLP-1 antagonized the senescence of endothelial cells evoked by 5FU. ERK1/2 was required for this protective effect of GLP-1 against 5FU-triggered senescence and eNOS downregulation, consistent with the previous data reporting the positioning this kinase downstream of GLP-1 (Favaro et al, 2012;Kang et al, 2015;Zhu et al, 2016). Experiments with multiple signalling inhibitors also suggested that the effect of GLP-1's action was secondary to PKA and PI3K, which have both been shown to mediate GLP-1's effects previously (Erdogdu et al, 2010;Oeseburg et al, 2010;Favaro et al, 2012;Chien et al, 2014;Zhu et al, 2016).…”
Section: Figuresupporting
confidence: 77%
See 1 more Smart Citation
“…Indeed, GLP-1 antagonized the senescence of endothelial cells evoked by 5FU. ERK1/2 was required for this protective effect of GLP-1 against 5FU-triggered senescence and eNOS downregulation, consistent with the previous data reporting the positioning this kinase downstream of GLP-1 (Favaro et al, 2012;Kang et al, 2015;Zhu et al, 2016). Experiments with multiple signalling inhibitors also suggested that the effect of GLP-1's action was secondary to PKA and PI3K, which have both been shown to mediate GLP-1's effects previously (Erdogdu et al, 2010;Oeseburg et al, 2010;Favaro et al, 2012;Chien et al, 2014;Zhu et al, 2016).…”
Section: Figuresupporting
confidence: 77%
“…Given the established role of ERK1/2 in GLP-1 signalling (Favaro et al, 2012;Kang et al, 2015;Zhu et al, 2016), we explored the effect of silencing ERK1/2 on the protective effect of GLP-1. ERK1/2 silencing prevented the GLP-1-induced inhibition of 5FU-induced senescence ( Figure 6A).…”
Section: Bjp P Altieri Et Almentioning
confidence: 99%
“…Activation of the PI3K/AKT pathway has been demonstrated to have neuroprotective effects against ischemia-induced neuron apoptosis (36). The Jak2/Stat3 cascade has been documented to be regulated by the PI3K/AKT pathway, mediating the functions in regulation of cell proliferation, anti-apoptosis and anti-senescence, cancer generation and migration, tissue development and memory formation (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT pathway is critically important in multiple physiological and pathological processes by regulating various downstream signaling molecules (36). Activation of the PI3K/AKT pathway has been demonstrated to have neuroprotective effects against ischemia-induced neuron apoptosis (36).…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca diğer çalışmalarda da orta serebral arter oklüzyonu sonrasında kan dolaşımını antioksidant etkisiyle artırdığı gösterilmiştir. Bu yararlı etkiler serbest oksijen radikallerinin azaltılması ve PI3K/Akt ve MAPK yolu ile ortaya çıktığı bildirilmektedir (21). Ob/ob, db/db farelerde ve yüksek yağ ile beslenen farelerde dentat girusdaki projentör hücre çoğalmasını artırarak nörogenezisi sağladığı gösterilmiştir (22) Parkinson hastalığının deneysel modellerinde ise eksendin-4 uygulamasının nörogenezisi, substantia nigradaki dopaminerjik nöron miktarını artırdığı gösterilmiştir (23).…”
Section: Glp-1'in Santral Sinirunclassified